The power of subtext making sense of literature - Yapo, Jerry R. (2012)
Readers' engagement with literature is enriched by focusing not only on the text and context, but also on the material's subtext. In the subtext lies a wellspring of meanings and interpretations that readers are privelaged to come up with, especially as these relate to three concerns: complexity in character motivations, testing the internal logic of narrative, and collocation of concepts in other disciplines. The goal is a dialogue with literary texts, empowering readers as the vital link in the interpretation process.